2006
DOI: 10.1016/j.joca.2006.03.017
|View full text |Cite
|
Sign up to set email alerts
|

MR measurement of articular cartilage thickness distribution in the hip

Abstract: The technique is reproducible, sensitive to sub-millimetre changes in thickness and may be useful in monitoring changes due to disease progression in patients with arthritis of the hip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 23 publications
4
50
1
Order By: Relevance
“…Cartilage strain has also been studied in vivo. Interestingly, it was reported that among studies in which a load was applied to the knee or hip for 2 to 4 h the mean magnitude of the recorded cartilage strain was smaller in the in vivo studies [10][11][12] than in the ex vivo studies [2,3,7]. For example, in a study of 6 normal specimens, Herberhold et al reported that the change in the maximal thickness of the knee joint cartilage was 2.8%, which was much smaller than that reported in ex vivo studies, probably due to the much shorter period of loading employed in the latter study [7].…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage strain has also been studied in vivo. Interestingly, it was reported that among studies in which a load was applied to the knee or hip for 2 to 4 h the mean magnitude of the recorded cartilage strain was smaller in the in vivo studies [10][11][12] than in the ex vivo studies [2,3,7]. For example, in a study of 6 normal specimens, Herberhold et al reported that the change in the maximal thickness of the knee joint cartilage was 2.8%, which was much smaller than that reported in ex vivo studies, probably due to the much shorter period of loading employed in the latter study [7].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to measure the cartilage thickness from MRI provides valuable potential to analyze the anatomy and biomechanics of diarthrodial joints, and perhaps more importantly, to study the progression of osteoarthritis (4)(5)(6). MRI-based quantitative cartilage thickness measurement techniques have become increasingly important in clinical applications as well as in fundamental research.…”
mentioning
confidence: 99%
“…The thickness of the acetabular cartilage was defined as the distance between the inner and outer cartilage edge positions. Naish et al (6) carried out the segmentation of the hip cartilage edges from MR images using a semi-automated method based on the livewire algorithm. The cartilage thickness was measured from the distance between the inner and outer cartilage edge positions.…”
mentioning
confidence: 99%
“…In order to precisely capture small morphological changes, particularly for the individual cartilage layer normally with 1∼3 mm thickness, this segmentation process must be performed with a high level of accuracy, robustness and reliability, which, in most clinical studies, was performed using fully manual or semi-automatic methods (Li et al 2008;Naish et al 2006). The disadvantages of these manual/semiautomated approaches are that they are very time-consuming and require skilled operators with considerable experience but still have considerable inter-and intra-rater variability, particularly under the influence of poor image quality, insufficient tissue contrast and various MR artefacts.…”
Section: Technical Motivationmentioning
confidence: 99%
“…To facilitate this, automated MR-based segmentation approaches are being developed to circumvent the need for extensive time-and expertise-intensive manual/semi-automated segmentation of osteochondral elements in the hip region (Kavanagh et al 2011;Naish et al 2006). In previous MR studies, advanced image analysis approaches such as SSM (Cootes et al 1995), atlas-based and graph search approaches have been successfully applied to automatic bone segmentation of the knee (Ababneh et al 2011;Fripp et al 2007;Shan et al 2012;Yin et al 2010), ankle (Li et al 2005) and spine ) and for use in subsequent segmentation of the cartilage Seim et al 2010).…”
Section: Introductionmentioning
confidence: 99%